2005
DOI: 10.1103/physrevlett.94.047003
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Vortex Motion in the Quantum-Liquid Phase of AmorphousMoxSi1xFilms

Abstract: We measure, in real time (t), the fluctuating component of the flux-flow voltage V(t), deltaV(t) identical withV(t)-V0, about the average V0 in the vortex-liquid phase of amorphous MoxSi1-x films. For the thick film, deltaV(t) originating from the vortex motion is clearly visible in the quantum-liquid phase, where the distribution of deltaV(t) is asymmetric, indicative of large velocity and/or number fluctuations of driven vortices. For the thin film the similar anomalous vortex motion is observed in nearly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…1͑d͔͒. 14 For the a-Mg x B 1−x film the T dependence of in different B and the phase diagram ͓Fig. 1͑e͔͒ obtained from ͑T , B͒ are qualitatively similar to those for the a-Mo x Si 1−x films.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…1͑d͔͒. 14 For the a-Mg x B 1−x film the T dependence of in different B and the phase diagram ͓Fig. 1͑e͔͒ obtained from ͑T , B͒ are qualitatively similar to those for the a-Mo x Si 1−x films.…”
supporting
confidence: 61%
“…14 We have suggested that the vortex dynamics in the QVL phase is dominated by quantum fluctuations. However, there is no theory that accounts for the finding comprehensively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our work clearly shows that S V is a very powerful tool to detect the phase transition(s) in the vortex-solid phase [14], where the linear resistance R is always zero, as well as in the liquid phase [16,17], which cannot be detected by ordinary static measurements (e.g., dc voltage V or R). From an experimental point of view, in order to detect such transitions clearly, we must select an appropriate value of V in measuring S V .…”
Section: Introductionmentioning
confidence: 97%